2018
DOI: 10.3904/kjim.2016.114
|View full text |Cite
|
Sign up to set email alerts
|

Long-term study of the association of adipokines and glucose variability with diabetic complications

Abstract: Background/AimsRecent studies have suggested an important role of adipokines in the development of insulin resistance and diabetes mellitus. The clinical relevance of adipokines on long-term outcomes in patients with diabetes and chronic kidney disease is uncertain. The purpose of this study was to identify a predictable factor in patients with long-term diabetic complications.MethodsA total of 161 diabetic individuals were followed-up from 2002 to 2013. Circulating plasma levels of adiponectin, glypican-4, ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…This is also consistent with the findings from experimental studies, which confirmed various benefits of irisin in patients with T2DM, such as anti-inflammation, improving insulin resistance, and possibly anti-atherosclerosis [11][12][13][14][15]. Besides, lower serum level of irisin has been observed in T2DM patients with macrovascular complications [16,17], while previous studies evaluating the association between serum irisin and DN showed inconsistent results [18][19][20][21][22][23][24][25][26][27][28][29][30]. Accordingly, we aimed to perform a meta-analysis to evaluate the association between serum irisin with albuminuria and reduced eGFR in T2DM patients.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is also consistent with the findings from experimental studies, which confirmed various benefits of irisin in patients with T2DM, such as anti-inflammation, improving insulin resistance, and possibly anti-atherosclerosis [11][12][13][14][15]. Besides, lower serum level of irisin has been observed in T2DM patients with macrovascular complications [16,17], while previous studies evaluating the association between serum irisin and DN showed inconsistent results [18][19][20][21][22][23][24][25][26][27][28][29][30]. Accordingly, we aimed to perform a meta-analysis to evaluate the association between serum irisin with albuminuria and reduced eGFR in T2DM patients.…”
Section: Introductionsupporting
confidence: 86%
“…Overall, 188 citations were identified through initial database search after excluding of duplications, of which 165 were excluded mainly because they were not relevant to the purpose of the study. The remaining 23 studies underwent full-text review, and 13 studies were finally included [18][19][20][21][22][23][24][25][26][27][28][29][30]. The other 10 studies were excluded based on the reasons listed in ▶ Fig.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…According to an experimental study, adipokines can lead to kidney injury by regulation of endothelial dysfunction, oxidative stress, and inflammatory processes (35). A longitudinal study of 161 subjects with diabetes followed from 2002 to 2013 demonstrated that plasma adiponectin increased in patients with renal insufficiency, and that its levels were positively associated with albuminuria (36). It is interesting to highlight that, in the context of chronic kidney disease, higher levels of adiponectin have been found to predict progression to end-stage renal disease (ESRD), cardiovascular mortality, and total mortality (37,38).…”
Section: Adiponectin and Metabolic Diseasesmentioning
confidence: 99%
“…Visfatin has been evaluated in the pathogenesis of diabetic nephropathy. Patients with renal failure in different stages were compared with each other, and a major difference was not observed between the patient groups[ 35 ]. However, in another study, high visfatin was associated with a decrease in kidney function in patients with diabetic nephropathy[ 36 ].…”
Section: Discussionmentioning
confidence: 99%